PRESERVATION OF COTTON FISH NET TWINES BY TANNING II. FIXATION OF TANNIN - CECILY, P J; KUNJAPPAN, M K (Fishery Technology, 2016)
Fix tiv beha iour of tannin belonging to three functional groups was stud1ed m deta1l using copper sulphate and potassium dichromate as oxidising agents.